(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the main changes in aesthetics and sexual function of patients with congenital penile curvature undergoing surgery using the Yachia method at Viet Duc University Hospital in the period 2018-2023. Research method: A prospective study. Research results: A total of 70 patients, with the mean age of 26.64 ± 7.24 years, undergoing surgery to correct congenital penile curvature were recruited into the study. Over 80% of patients reported that they were admitted to the hospital for aesthetic reasons related to their curved or unusual penis. The majority of patients (81.43%) had curvature in only one direction, with the mean angle of 45.13 ± 11.26 degrees. After surgery, there was a significant improvement in penile curvature aesthetically, although there was also a reduction in penis length (p < 0.001) with an average shortening of 1.4 ± 0.3 cm. In terms of sexual function, surgery for congenital penile curvature was found to improve both sexual intercourse status (p = 0.014) and sexual intercourse ability (p < 0.001). Conclusion: The surgery to correct congenital penile curvature using the Yachia method is an effective and safe way to improve the patient’s aesthetics and sexual function.